The differentiated workforce : transforming talent into strategic impact - Becker, Brian E.; Huselid, Mark A., 1961-; Beatty, Richard W. (Boston, Mass. : Harvard Business Press, 2009)
In 'The Differentiated Workforce', the authors expand on their previous books, 'The HR Scorecard' and 'The Workforce Scorecard', and recommend that you manage your workforce like a portfolio - with disproportionate investments in the jobs that create the most wealth.
Put strategy first, not people -- Link workforce strategic capabilities to workforce strategy -- Identify strategic positions -- Establish leadership accountability for workforce success: the line manager's HR role -- Design an HR architecture for the differentiated workforce -- Develop straegic workforce measures -- Make it happen in practice: creating a differentiated workforce at the American Heart Association.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Personnel management; Human capital -- Management; Strategic planning; Organizational effectiveness; Strategisches Management; Personalwirtschaft; Hochqualifizierte Arbeitskräfte; Spojené státy americké; Human capital -- Management; Organizational effectiveness; Personnel management; Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books